Calcium/calmodulin-dependent protein kinase IV limits organ damage in hepatic ischemia-reperfusion injury through induction of autophagy - John Evankovich; Ruilin Zhang; Jon Cardinal; Lemeng Zhang; Jun‐Da Chen; Hai Huang; Donna Beer–Stolz; Timothy R. Billiar; Matthew R. Rosengart; Allan Tsung (2012)
Sterile inflammatory insults, such as ischemia-reperfusion (I/R) injury, result from pathogenic factors, including damage-associated molecular pattern signaling, activation of innate immunity, and upregulation of proinflammatory cytokines. At the same time, a number of protective, or prosurvival, pathways are also activated, and the extent of end-organ damage is ultimately determined by the balance between these two systems. In liver I/R, members of the calcium/calmodulin-dependent protein kinase (CaMK) family are known to be activated, but their individual roles are largely unknown. In this study, we show that one CaMK member, CaMKIV, is protective in hepatic I/R by activating the prosurvival pathway of autophagy in hepatocytes. CaMKIV knockout mice experience significantly worse organ damage after I/R and are deficient in hepatocyte autophagic signaling. Restoration of autophagic signaling with rapamycin reduces organ damage in CaMKIV knockout mice to wild-type levels. In vitro, we show that CaMKIV activation induces autophagy in mouse hepatocytes, and that CaMKIV activation protects hepatocytes from oxidative stress-induced cell death. In conclusion, the protective autophagic signaling pathway serves to reduce organ damage following I/R and is regulated by activation of CaMKIV signaling in hepatocytes.